Electrophoretic Analysis of Seed Proteins from Different Varieties of Rice Cultivated in Sindh - Tahir Ansari, Ibtessam; Sahito, Mumtaz Ali; Ghanghro, A.B.; Memon, A.N.; Khan, Shaista (Pakistan Journal of Nutrition, 2011)
SDS-PAGE electrophoresis is the most effective as well as one of the simplest methods for separating proteins. The extraction and fractionation technique was applied to characterize rice seed proteins. Identification and screening of rice proteins carried out from 14 varieties of rice collected from Nuclear Institute of Agriculture (NIA) Tandojam. Rice seed proteins were extracted with phosphate buffer for total proteins. After quantification, proteins were separated by SDS-PAGE Electrophoresis. Analysis of rice seed proteins was performed on the results of SDS-PAGE using gel documentation system (Biorad) to find out the molecular weight of different varieties of rice followed by cluster analysis using SPSS to find out the diversity among different rice varieties.